Intestinal Microbiota Modulation in Obesity-Related Non-alcoholic Fatty Liver Disease - Porras, David; Nistal, Esther; Martínez-Flórez, Susana; González-Gallego, Javier; García-Mediavilla, María Victoria; Sánchez-Campos, Sonia (Frontiers in Physiology, 2018)
Obesity and associated comorbidities, including non-alcoholic fatty liver disease (NAFLD), are a major concern to public well-being worldwide due to their high prevalence among the population, and its tendency on the rise point to as important threats in the future. Therapeutic approaches for obesity-associated disorders have been circumscribed to lifestyle modifications and pharmacological therapies have demonstrated limited efficacy. Over the last few years, different studies have shown a significant role of intestinal microbiota (IM) on obesity establishment and NAFLD development. Therefore, modulation of IM emerges as a promising therapeutic strategy for obesity-associated diseases. Administration of prebiotic and probiotic compounds, fecal microbiota transplantation and exercise protocols have shown a modulatory action over the IM. In this review we provide an overview of current approaches targeting IM which have shown their capacity to counteract NAFLD and metabolic syndrome features in human patients and animal models.